Strength-based counseling as self-help method to overcome Nomophobia and FoMo among students - Suranata, Kadek; Ifdil, Ifdil; Bolo Rangka, Itsar; Abu Bakar, Abu Yazid; Subramaniam, Tamil Selvan (Universitas Negeri Padang, 2022)
Student mental health and psychological well-being have become a concern nowadays. A recent study reported that during the Covid-19 pandemic, there is an emergence of emotional and psychological disorder experienced by adolescents and students around the world that relates to the high use of the internet and social media. This study aimed to report the effectiveness of self-help strength-based counseling (SBC) to overcoming Nomophobia and Fear of Missing Out (FOMO) among students. By following the RCT’s procedure, this study involved a total of 418 high school students as participants. Through randomized sampling, two experimental groups and one control group were obtained. The first experimental group participated in SBC through a learning management system (LMS), the second experimental group participated in SBC through the paper-based module, and the waiting-list control group did not participate in any interventions. The results of this study show that the LMS-based self-help SBC method and the paper-based module SBC were effective interventions to overcome nomophobia and FoMO among students. The results of this study have implications for the use of self-help methods in counseling services.